PENGARUH PENAMBAHAN SARI BUAH TERTENTU TERHADAP KARAKTERISTIK FISIK, KIMIA, DAN SENSORI SARI TOMAT - Riyan Arip Wibowo; Fibra Nurainy; Ribut Sugiharto (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The objectives of this research were to find out the physical, chemical, and sensory characteristics of the mixed tomato juice produced and to determine the suitable fruit for tomato mixed juice. The experiment was arranged in a  completely randomized block design with 4 replications.  The fruit mixed with the tomato juice was either peanapple, orange, red guava, mango, passion fruit, or soursop.  The formulation of  mixture contained of 60 % of tomato juice and of 40 % added fruits juice.  The result showed that the addition of fruits juice to the tomato juice significanty affected color, flavor, taste, overall acceptance, pH, total dissolved solid, vitamin C, and stability of mixed juice.  More over the addition of red guava resulted in the best characteristic of mixed tomato juice. The formulation of tomato juice mixed with red guava gave the most acceptable.  The mixed juice of guava and tomato had pH of 4,4, total dissolved solid of 6,90 Brix, level stability of 0,53, antioxidant activity of 87,727%, and vitamin C of  60,4 mg/100g . Keywords:  antioxidant activity, mixed-fruit juice, red guava, tomato.